Controversial issues in adventure programming - Martin, Bruce, 1969-; Wagstaff, Mark, ....- (Champaign, Ill. : Human Kinetics, 2012)
Controversial Issues in Adventure Programming offers an engaging approach to the consideration of enduring, current, and emerging issues in the field. Written primarily for upper-level undergraduate and graduate students, the text presents 20 issues in a debate format, challenging students to participate in critical discourse concerning these issues as practitioners in the field of adventure programming. Respected authors Bruce Martin and Mark Wagstaff have assembled a team of more than 50 contributors from around the globe to reassess some of the underlying assumptions on which adventure programming is based. They have critically examined implications of new developments for emerging practice and discussed how best to position the field of adventure programming in addressing broader societal concerns. To set the stage for the debate, each issue is prefaced with a general overview, including the evolution of the issue and its significance in light of broader social concerns. Then, contributors present the pros and cons of each issue. A debate format helps students develop an understanding of the key points around each issue while also becoming familiar with current research pertinent to these issues. This approach also encourages students to grapple with these issues and begin to develop their own informed, thoughtful perspectives as they prepare for careers in adventure programming. Controversial Issues in Adventure Programming is divided into two parts. Part I begins by discussing issues of ongoing concern in the field, including the certification debate, motorized versus nonmotorized forms of outdoor recreation, and program accreditation. In part II, contemporary and emerging issues are presented, such as the use of online educational programming in the field of adventure programming. As a reference for practitioners and policy makers, Controversial Issues in Adventure Programming offers new an
Part II.Contemporary and Emerging Issues Issue 11. Should extreme sports, such as BASE jumping and other high-risk sports, be included in adventure programming? Issue 12. Should nonprofit and educational programs be required to obtain permits to use public land? Issue 13. Should Wilderness First Responder be the standard of care for wilderness leadership? Issue 14. Should wilderness program staff always accompany their participants? Issue 15. Should transgender youths be encouraged to favor specialized camps over mainstream camps? Issue 16. Does Leave No Trace make a difference beyond the scope of back country environmental practices? Issue 17. Are educational reform policies that stress standards and accountability compatible with pedagogical aims and practice in outdoor education? Issue 18. Are rational decision-making models the most effective method to train novice outdoor leaders? Issue 19. Is it possible to effectively accomplish the goals of outdoor education through online programming? Issue 20. Is outcomes-based research currently more important than critical research for the field of adventure programming?
Includes bibliographical references.
Keywords: Adventure education; Buitensporten; Ervaringsleren